Efek Komunikasi Pemasaran Terhadap Minat Melanjutkan Studi Di STIkes KHAS Kempek Dengan Citra Kampus Dan Kualitas Pendidikan Sebagai Variabel Intervening - Arwani, Muhammad; Fitriani, Lili Karmela; Rahmantya, Yanneri Elfa Kiswara (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
Research Objectives are: 1) test the influence of marketing communications on campus images 2) test the impact of marketing communication on further study interests 3) test the effect of education quality on campus image 4) test the effects of campus images on further studies interests 5) test the quality of education on continuing study interest 6) test campus images in mediating the influences of market communication on student interests 7) test educational quality can mediate the influencing of marketing kommunikation on study interest. The population on this study is eleventh grade student MA KHAS Kempek by 2024 of 450 students. Sampling technique using proportional random sampling. The calculation of the number of samples using the Slovenian formula with a rate of error or a tolerable percentage of lack of study of 5% obtained a sample of 228 students. Research results are: 1) marketing communication has a positive and significant influence on campus image 2) marketing communications have a positive, significant impact on further interests of study 3) marketing communication have a significant and positive impact on the quality of education 4) campus image has no effect on further study interests 5) education quality has no influence upon further interest of study 6) campus image is able to partially mediate the influence of marketing communication on the further interest process of study 7) education quality is capable of mediating the impact of market communication on further studies interests.